Post-Stroke Rehabilitation Education at the ILP Dahlia Integrated Health Post (Posyandu) in Pelem Village, Pare District, Kediri Regency Family Empowerment Strategy Approach - Dwi Rahayu; Erni Rahmawati; Luluk Susiloningtyas (Journal of Community Engagement in Health, 2025)
Stroke is a brain dysfunction that occurs suddenly due to disruption of blood flow to the brain, and this condition can be experienced by anyone, at any time. In Indonesia, the prevalence of stroke has increased from 7% to 10.9%. It is estimated that around 500,000 people suffer from stroke each year, with around 25% dying and the remaining 75% experiencing hemiparesis, which is muscle weakness on one side of the body. At the ILP Dahlia Integrated Health Post (Posyandu), there are 10 elderly people who experience weakness and are unable to carry out activities due to stroke. The purpose of this community service is to provide education about post-stroke rehabilitation for the elderly. The community service method used is providing education to participants. The number of community service participants was 35 elderly people at the ILP Dahlia Integrated Health Post, Pelem Village, Pare District, Kediri Regency. The results of the Community Service showed an increase in knowledge of community service participants after the counseling on post-stroke rehabilitation for the elderly, with an increase in knowledge in the good category of 71% compared to before the counseling the knowledge was in the good category of 5%. Knowledge is the basis for someone in making a decision because it is related to a person's ability to make the right choice, where knowledge is the basis for forming behavior.